THE IMPACT OF COVID-19 ON THE PRODUCTION AND INCOME OF HYBRID CORN (Zea mays L) FARMER IN WATANG KASSA VILLAGE, BATULAPPA DISTRICT, PINRANG REGENCY - Dwi Ahrisa Putri; Kaimuddin Kaimuddin; Hartina Hartina (AGROLAND The Agricultural Sciences Journal (e-Journal), 2023)
Pinrang Regency is one of the centers for the development of Hybrid Corn (Zea mays L) which is spread in several sub-districts, including Batulappa District, as BPS listed the largest shelled corn producing area in Pinrang Regency. Corn production in 2016-2018 continued to increase successively, were in 2018 it was able to produce shelled corn of 56,185 tons. The Covid-19 pandemic has had an impact on several sectors, one of which is the agricultural sector. This study aims to analyze the impact of the Covid-19 pandemic on the production and income of hybrid corn farmers in Watang Kassa Village, Batulappa District, Pinrang Regency. The area was chosen because it is the largest corn producing area and the majority of the surrounding population depend on corn farming. The data collected in this study are primary data and secondary data. Primary data was obtained through interviews with respondents using questionnaires, while secondary data is obtained indirectly or through intermediary media, data that has been available in various forms by relevant government agencies. Total sample in this study were 42 corn farmers. Researchers used descriptive quantitative methods through interviews with farmers and filling out questionnaires as a support to obtain data. Corn farming was analyzed using income analysis and further with hypothesis testing, namely the Paired Sample T-Test average difference test. The results showed that there was a real or significant difference in corn production and there was an average decrease in corn production by 537/kg while the average income of corn farmers increased by IDR 1,097,000.